How to calculate it?

Calculus Level 5

0 1 { ( 1 ) 1 x 1 x } d x \large \displaystyle \int_0^1 \left\{(-1)^{\left\lfloor \frac{1}{x}\right\rfloor}\cdot\dfrac{1}{x}\right\}\, dx

The integral above has a closed form. Find the value of this closed form.

Give your answer to 3 decimal places.

Notations:


The answer is 0.548.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

First Last
Dec 9, 2016

0 1 { ( 1 ) 1 x 1 x } d x = 1 ( 1 ) x x ( 1 ) x x x 2 d x by 1 x x \displaystyle \int_0^1 \left\{(-1)^{\left\lfloor \frac{1}{x}\right\rfloor}\cdot\dfrac{1}{x}\right\}dx = \int_{1}^{\infty}\frac{(-1)^{\lfloor x\rfloor}x - \lfloor (-1)^{\lfloor x\rfloor}x\rfloor}{x^2}dx\quad\text{ by }\frac{1}{x}\rightarrow x

Split into regions of floor(odd.xyz) = odd and floor(even.xyz) = even

n = 1 2 n 1 2 n 1 x d x + 2 n 2 n + 1 1 x d x n = 1 2 n 1 2 n 2 n x 2 d x + 2 n 2 n + 1 2 n x 2 d x = \displaystyle\sum_{n=1}^{\infty}\int_{2n-1}^{2n}\frac{-1}{x}dx+\int_{2n}^{2n+1}\frac{1}{x}dx-\sum_{n=1}^{\infty}\int_{2n-1}^{2n}\frac{-2n}{x^2}dx+\int_{2n}^{2n+1}\frac{2n}{x^2}dx =

n = 1 ln ( 2 n ) + ln ( 2 n 1 ) + ln ( 2 n + 1 ) ln ( 2 n ) + n = 1 2 n 2 n 1 + 2 n 2 n + 1 2 = \displaystyle\sum_{n=1}^{\infty}-\ln{(2n)}+\ln{(2n-1)}+\ln{(2n+1)}-\ln{(2n)} + \sum_{n=1}^{\infty}\frac{2n}{2n-1}+\frac{2n}{2n+1}-2 =

ln ( n = 1 1 1 4 n 2 ) + n = 1 1 2 n 1 1 2 n + 1 \ln{\big( \prod_{n=1}^{\infty}1-\frac1{4n^2}\big)} + \sum_{n=1}^{\infty}\frac{1}{2n-1}-\frac{1}{2n+1}

n = 1 1 1 4 n 2 = 2 π \displaystyle\prod_{n=1}^{\infty}1-\frac1{4n^2} = \boxed{\frac{2}{\pi}} from the Wallis Product

n = 1 1 2 n 1 1 2 n + 1 = n = 1 0 1 ( y 2 ) n 1 d y ( y 2 ) n d y = 0 1 n = 1 ( y 2 ) n 1 d y ( y 2 ) n d y = \displaystyle\sum_{n=1}^{\infty}\frac{1}{2n-1}-\frac{1}{2n+1} = \sum_{n=1}^{\infty}\int_{0}^{1}(y^2)^{n-1}dy-(y^2)^ndy =\int_{0}^{1}\sum_{n=1}^{\infty}(y^2)^{n-1}dy-(y^2)^ndy =

0 1 1 1 y 2 ( 1 1 y 2 1 ) = 1 \displaystyle\int_{0}^{1}\frac{1}{1-y^2}-( \frac{1}{1-y^2}-1) = \boxed{1}\quad by noticing the infinite geometric sequence and reversing the sum and integral.

ln 2 π + 1 . 548 \displaystyle\Huge\ln{\frac{2}{\pi}}+1 \approx \boxed{.548}

p.s. Great problem!

I have done upto ln ( 1 1 4 a 2 ) \ln(\frac{1}{1-4 a^2}) but I didn;t know Wallis Product.So ,I can not solve

Kushal Bose - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...